Goodbye mom & dad see you in the afternoon : one-stop preschool parenting solutions - Selot, Dr Bindu (Delhi : Sterling Publishers Pvt. Ltd, 2015)
About the book: goodbye mom and dad see you in the afternoon with the help of her successful case studies and well-designed strategies, the author shares her tried and tested parenting solutions for young parents, based on her experience of 22 years with parents from all over the country. This book is meant for all the parents whose children are already going to preschool or are about to start preschooling. It is also meant for all the other significant adults in a childs life-the preschool educators, teachers, and counsellors. The contents of this book will give you an insight into what all needs to be done so that you can maximize on the preschool years of your children and help them make the extensive learning pathways, not by accident but by design, because it is you who creates the environment of the children.
Includes bibliographical references.
Keywords: Preschool parenting